2021
DOI: 10.13057/biodiv/d220346
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of fungi associated with rhizosphere of healthy and diseased garlic crop

Abstract: Abstract. Hidayah BN, Herawati N, Aisah AR, Utami NR. 2021. Diversity of fungi associated with rhizosphere of healthy and diseased garlic crop. Biodiversitas 22: 1433-1440. Garlic (Allium sativum L.) is an especially important horticultural crop in Indonesia because it is used as a cooking spice and for medicines and cosmetic ingredients. It is mostly grown in irrigated highlands; however Indonesian production is only supplying at most 17.5% of domestic demand. West Nusa Tenggara (WNT) Province is one of the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Hyphae are septate, branched mycelium is usually colorless, conidia oval shape is a specific feature of the fungus Penicillium sp. (Ratnawati et al 2020;Hidayah et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Hyphae are septate, branched mycelium is usually colorless, conidia oval shape is a specific feature of the fungus Penicillium sp. (Ratnawati et al 2020;Hidayah et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…was mainly found on manii and pine wood samples since the first month of feeding. Hidayah et al (2021) stated that Aspergillus is a fungus commonly found in soil and overgrows and is antagonistic to other fungi. Its mechanisms occur through competition, mycoparasitic, and antibiosis.…”
Section: Fungi Species That Attack Wood Samplementioning
confidence: 99%
“…Observations both macroscopically and microscopically correspond to the characteristics of Fusarium sp. The characters were mycelium proliferates in cultures resembling cotton, and often the mycelium is slightly pink, purple, or yellow in the media; variation in conidiophores, having a cylindrical shape, simple or strong, short, irregularly branched or connected to a phyalida, or collected in sporodochia; hyaline conidia, two forms often attached to the tips; the macroconidia consist of several cells, have a slightly curved shape or are bent at the ends; single-cell microconidia have an ovoid shape, single or in chains; some conidia sometimes consist of 2 or 3 cells, rectangular or slightly curved (Hidayah et al 2021). According to Funder (1953), conidia develop directly on the side of the hyphae without any detectable conidiophores called sessile and lateral (on the sides).…”
Section: Identification Of Pathogenic Fungi Carried By Pests and Pred...mentioning
confidence: 99%
“…Penicillium sp. has septate hyphae and forms conidia (Hidayah et al 2021). Conidia have branches called phialides, which look like a bubble (Mirsam et al 2022).…”
Section: Penicillium Spmentioning
confidence: 99%
See 1 more Smart Citation